The bidirectional tumor: mesenchymal stromal cell interaction promotes the progression of head and neck cancer - Kansy, Benjamin Alexander; Dißmann, Philip A.; Hemeda, Hatim; Bruderek, Kirsten; Westerkamp, Anna M.; Jagalski, Vivien; Schuler, Patrick; Kansy, Julia Katharina; Lang, Stephan; Dumitru, Claudia A.; Brandau, Sven (Stem cell research & therapy, 2014)
Mesenchymal stromal cells (MSC) are an integral cellular component of the tumor microenvironment. Nevertheless, very little is known about MSC originating from human malignant tissue and modulation of these cells by tumor-derived factors. The aim of this study was to isolate and characterize MSC from head and neck squamous cell carcinoma (HNSCC) and to investigate their interaction with tumor cells.
Gesehen am 25.08.2020